Comparison of In Vivo Tissue Temperature Profile and Lesion Geometry for Radiofrequency Ablation With High Power–Short Duration and Moderate Power–Moderate Duration: Effects of Thermal Latency and Contact Force on Lesion Formation - Nakagawa, Hiroshi; Ikeda, Atsushi; Sharma, Tushar; Govari, Assaf; Ashton, John; Maffre, Jennifer; Lifshitz, Alexander; Fuimaono, Kristine; Yokoyama, Katsuaki; Wittkampf, Fred H.M.; Jackman, Warren M. (Circulation. Arrhythmia and electrophysiology, 2021)
[Figure: see text].